Low incidence of hypercalcemia following combined calcipotriol hydrate/betamethasone dipropionate ointment treatment in Japanese patients with severe psoriasis vulgaris. (4th July 2018) - Morita, Akimichi; Muramatsu, Shinnosuke; Kubo, Ryoji; Ikumi, Kyoko; Sagawa, Yoko; Saito, Chiyo; Torii, Kan; Nishida, Emi
Abstract: Purpose: Topical active vitamin D3 application alone or in combination with topical steroid application is widely used to treat psoriasis. In Japan, combined calcipotriol hydrate/betamethasone dipropionate ointment has been used for patients with psoriasis vulgaris since September 2014. Current evidence regarding the incidence of hypercalcemia due to the use of this combination product, however, is insufficient. We evaluated the incidence of hypercalcemia following combined calcipotriol hydrate/betamethasone dipropionate ointment in patients with severe psoriasis vulgaris. Methods: Japanese patients ( n = 22) with extensive plaque psoriasis (body surface area: 20–30%) applied the combined calcipotriol hydrate/betamethasone dipropionate ointment once daily for 8 weeks, and their serum Ca concentrations were measured periodically. Results: The mean serum Ca concentration changed only marginally, from 9.04 ± 0.34 mg/dL before treatment to 9.08 ± 0.39 mg/dL after 8 weeks of treatment. None of the patients had an elevated serum Ca concentration throughout the study. No cases of hypercalcemia were reported as an adverse event. No correlation was detected between the amount of the combined calcipotriol hydrate/betamethasone dipropionate ointment applied and changes in the serum Ca concentration. Conclusion: The incidence of hypercalcemia due to topical application of a combined calcipotriol hydrate/betamethasone dipropionate ointment is low in Japanese patients with severe psoriasis vulgaris.